2017
DOI: 10.1530/ec-17-0304
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic healthy and unhealthy obesity: does vitamin D play a role?

Abstract: ObjectiveThe aim of this observational study was to clarify the link between vitamin D status and metabolic syndrome (MetS) in people with visceral obesity.Design and methodsOne hundred ninety-six consecutive patients (152 women; mean age 51 ± 13 years) with visceral obesity (mean body weight 103 ± 20 kg, mean waist circumference (WC) 119 ± 13 cm) were enrolled at the Obesity Outpatient Clinic of the University of Insubria in Varese. Anthropometric measurements were recorded. Laboratory tests, including vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
2
9
0
3
Order By: Relevance
“…This is in agreement with the findings of a study by Piantanida et al who reported no significant difference in LDL-C levels among patients with vitamin D levels <10 ng/mL, 10-20 ng/mL and ≥20 ng/mL. 23 The average LDL-C levels in our study were found to be <100 mg/dL in both groups, i.e., statin users with SAMS and statin users without SAMS. Additionally, no association was found between the levels of LDL-C (<100 mg/dL and ≥100 mg/dL) and the occurrence of SAMS among statin users.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the findings of a study by Piantanida et al who reported no significant difference in LDL-C levels among patients with vitamin D levels <10 ng/mL, 10-20 ng/mL and ≥20 ng/mL. 23 The average LDL-C levels in our study were found to be <100 mg/dL in both groups, i.e., statin users with SAMS and statin users without SAMS. Additionally, no association was found between the levels of LDL-C (<100 mg/dL and ≥100 mg/dL) and the occurrence of SAMS among statin users.…”
Section: Discussionsupporting
confidence: 93%
“…Плейотропна дія вітаміну була відзначена багатьма спостереженнями, що свідчить про існуючий зв'язок між низькою концентрацією 25(OH)D і підвищеним ризиком онкологічних (зокрема, раку кишечника, молочних залоз, яєчників, простати, підшлункової залози, шкіри, нирок, мозку, численних різновидів мієломи й лейкемії) [74][75][76][77][78], імунологічних захворювань (розсіяного склерозу [79][80][81][82], астми [83,84], неспецифічного запального захворювання кишечника [85,86] й системного червоного вовчака [87,88]), автоімунних ендокринних порушень (діабет І типу [89,90], хвороба Аддісона [91,92], хвороба Хашімото [93,94], Базедова хвороба, хвороба Грейвса [95,96] й автоімунні поліендокринні синдроми [97]), імунодефіциту й рецидивуючих інфекцій [98] (зокрема, туберкульозу й грипу), компонентів метаболічного синдрому (артеріальної гіпертензії, серцево-судинних хвороб, атеросклерозу, ішемічної хвороби серця, діабету І типу, ожиріння) [99][100][101][102][103][104][105], психіатричних порушень (депресія [106], шизофренія [107,108]), нейродегенеративних хвороб (деменція [109][110][111], хвороба Альцгеймера [112,113], порушення когнітивної функції [109,110,…”
Section: кальціємічний ефект вітаміну Dunclassified
“…Aspekt działania plejotropowego witaminy D testowano w licznych badaniach obserwacyjnych, które sugerują istnienie związku między niskim stężeniem 25(OH)D w surowicy a zwiększonym ryzykiem nowotworów (między innymi okrężnicy, piersi, jajnika, prostaty, trzustki, skóry, guzów mózgu, nerek, szpiczaka mnogiego, białaczki) [73][74][75][76][77], chorób o podłożu immunologicznym (stwardnienie rozsiane [78][79][80][81], astma oskrzelowa [82,83], nieswoiste choroby zapalne jelit [84,85], toczeń rumieniowaty układowy [86,87], w tym autoimmunizacyjnych zaburzeń endokrynnych (cukrzyca typu 1 [88,89], choroba Addisona [90,91], choroba Hashimoto [92,93], choroba Gravesa-Basedowa [94,95], autoimmunologiczne zespoły niedoczynności wielogruczołowej [96]), zaburzeń odporności i nawracających infekcji [97] (między innymi gruźlicy i grypy), chorób cywilizacyjnych (w tym nadciśnienia tętniczego i chorób układu sercowo-naczyniowego, miażdżycy, choroby niedokrwiennej serca, cukrzycy typu 2, otyłości) [98][99][100][101][102][103][104], a także zaburzeń psychiatrycznych (depresji [105], schizofrenii [106,107]) oraz chorób neurodegeneracyjnych (demencji 108-110], choroby Alzheimera [111,112], obniżenia funkcji poznawczych [108,…”
Section: Działanie Plejotropowe Witaminy Dunclassified